Toughening of epoxies by covalently anchoring triazole-functionalized stacked-cup carbon nanofibers - Ding, Guoqiang (2013)
Novel triazole-functionalized carbon nanofibers (m-CNFs) were prepared by one-step arylation with diazonium salts generated in situ. Microscopic observations indicate that m-CNFs exhibit significantly improved dispersibility in a high-performance epoxy resin compared with pristine CNFs (p-CNFs). The results of DSC and SEM show evidence of interfacial reaction and a more robust interface between m-CNFs and the epoxy matrix. Thermal and mechanical properties of two CNF/epoxy composites were systematically studied at different filler loadings. The results show that both CNF fillers could reinforce the epoxy matrix without sacrificing their thermal properties. Benefiting from the improved dispersibility and interfacial interaction, the ability of m-CNFs in toughening the epoxy resin is clearly superior to p-CNFs. The addition of only 0.4 wt% m-CNFs gives 41 and 80% enhancement in critical stress intensity factor (KIC) and the critical strain energy release rate (GIC), respectively.